“The Concept of Folk Literature and Its Artistic Trends.” - rehmoun, bouzid (El Omda in Linguistics and Discourse Analysis, 2021)
Abstract :This study seeks to approach popular literature as a branch of heritagerelated to human experiences, knowledge, feelings and itavailable to man in his artistic forms and creative productions, which have a fundamental role with in society.The investment of popularliteraturewithinitsheritagecontextsprovides the possibility of achieving cultural communication between a pastthatrepresents the origin and history, and a presentlinked in terms of itssignificance to interacting human and social dimensions thatseek to express the individual's problems within his socio-cultural reality and in light of the immediate and future variables. Popular literature, artistic discourse, content, spécialisation, and production